Healthy Eating: Fluids - Linda B. Bobroff (EDIS)
More than one-half of an adult’s body weight is water. Water brings nutrients to the cells in our bodies and removes waste. Our bodies cannot function if they do not receive enough water. This 2-page fact sheet is a major revision that addresses the importance of water to physical functions, effects of dehydration, risk factors for dehydration in older adults, and fluid intake suggestions. Written by Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, June 2016.